'I found it the only place that spoke the same language': a thematic analysis of messages posted to an online peer support discussion forum for people living with dementia. (14th January 2023) - Talbot, Catherine V; Coulson, Neil S
Abstract: Background: Despite the proliferation of online support communities, little is known about how people with dementia engage with them. Aim: The aim of this study was to explore the content of messages exchanged between members of the asynchronous Talking Point online discussion forum. Method: Using the sub-forum 'I have dementia', 100 conversation threads were randomly selected yielding 863 individual messages for analysis. Our data set was subjected to reflexive thematic analysis. Results: Three themes were generated: journeying through dementia, reciprocal peer support and therapeutic creativity. The findings suggest that individuals used the forum to share their experiences of obtaining and adjusting to a dementia diagnosis, their current symptoms and how they addressed the challenges of daily living as well as the impacts on mood, confidence and connectedness. The forum was viewed as a safe space to reflect on the future and what it might hold for them and loved ones. Throughout these discussions, users supported each other, particularly in relation to the emotional impact of diagnosis and shared experiential information and advice, with referrals to external sources of support commonplace. Discussion around the role of therapeutic creativity was evident and its role as a coping mechanism described. Through engagement, a sense of community and companionship was evident and new members welcomed, supported and encouraged to join in. Discussion: The forum appears to be filling an important gap in post-diagnostic support provision, particularly for those with rare forms of dementia. Clinicians, support workers and organisations could consider recommending online support forums to people with dementia.